Pengaruh Tingkat Pemahaman Pajak, Omset Penghasilan dan Digitalisasi Pelayanan Terhadap Kepatuhan Wajib Pajak (studi kasus pelaku UMKM Mitra Mandiri Brebes) - Moh. Khusen Nur Iman; Titi Rahmawati; Roni Roni (Universitas Katolik Widya Karya Malang, 2023)
Taxes play an important role in state revenue, through the rapid development of economic sectors and have the potential to increase tax revenue. According to the Small and Medium Enterprises Cooperative Office of Central Java Province, Brebes Regency has MSMEs with a total of 8385 units. With so many MSME actors who should be able to meet taxpayer compliance due to the lack of tax knowledge, the development of digitalization and MSME actors in Brebes Regency. This study aims to determine the effect of the level of tax understanding, income turnover and digitalization of services on tax compliance of taxpayers of micro, small and medium enterprises (MSMEs) Mitra Mandiri Brebes. This research was conducted at MSMEs Mitra Mandiri Brebes. This research method is quantitative research. This study used purposive sampling method. The analysis technique used is multiple linear regression. The results showed that the level of tax understanding had a significant positive direction with a large influence of 59%; while income turnover has a significant direction of 68%; and digitalization of services has a significant positive direction of 49%